2012
DOI: 10.1128/mcb.00851-12
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1α Regulates an MDMX Intramolecular Interaction To Stimulate p53 Binding

Abstract: MDMX is an important regulator of p53 during embryonic development and malignant transformation. Previous studies showed that casein kinase 1␣ (CK1␣) stably associates with MDMX, stimulates MDMX-p53 binding, and cooperates with MDMX to inactivate p53. However, the mechanism by which CK1␣ stimulates MDMX-p53 interaction remains unknown. Here, we present evidence that p53 binding by the MDMX N-terminal domain is inhibited by the central acidic region through an intramolecular interaction that competes for the p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…CK1α disrupts this intramolecular interaction, stimulating N-terminal binding to p53. DNA damage inhibits the MDMX-CK1α interaction (13), thus enhancing the MDMX internal binding to conceal the p53-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CK1α disrupts this intramolecular interaction, stimulating N-terminal binding to p53. DNA damage inhibits the MDMX-CK1α interaction (13), thus enhancing the MDMX internal binding to conceal the p53-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study suggested that the MDMX AD regulates the N-terminal domain (13). Inspection of the MDMX sequence identified two central regions with hydrophobic residues that may serve as p53 mimetics (Fig.…”
Section: Detection Of Mdmx Intramolecular Interactions Using Pfr Assaymentioning
confidence: 99%
See 3 more Smart Citations